Численное моделирование конвективного теплообмена и аэродинамики поверхностей с пластинчато-разрезным оребрением - Баранюк, Александр Владимирович; Рогачов, Валерий Андреевич; Терех, Александр Михайлович; Руденко, Александр Игоревич (НТУ "ХПИ", 2017)
Представлены результаты CFD-моделирования теплообмена и аэродинамического сопротивления пластинчато-ребристых поверхностей с разрезными ребрами в условиях вынужденной конвекции. Получены данные численного расчета средней теплоотдачи и аэродинамического сопротивления теплоотводящих поверхностей. Доказано, что разрезка повышает интенсивность теплообмена в 1,16-1,25 раза при одновременном росте аэродинамического сопротивления в 1,25-1,35 раза по сравнению с пластинчато-ребристой поверхностью без разрезки. Показана приемлемая сходимость результатов опытных и численных исследований.

Providing optimal modes for the cooling of the elements of radio-electronic equipment (REE), personal computers (PC) and other heat-stressed elements of electronic equipment is a vital problem the solution of which will provide their reliable functioning. Different methods are used for the solution of this problem, but the method of forced air cooling still remains to be the simplest, cheapest and easy-to-use. To increase the air cooling efficiency of the elements of REE and PC we use at the present time extended heat removal surfaces in the form of a flat base with plate ribs and needle-pin ribs fixed to it that increasingly fail to meet the requirements of a maximum heat removal and temperature drop on the heat-strained element. Therefore, the researchers and the designers have to solve an important problem to increase the thermal efficiency of heat exchange of such small-size surfaces. This scientific paper describes the method of the intensification of heat emission due to the partial splitting of lamellar ribs along their height. This would allow us to create conditions for the initiation of separation of the boundary layer on the flat surface of the ribs, decrease the layer thickness and turbulize the flow passing over the ribbed surface. The research was done using the CFD models of lamellar-ribbed surfaces with split ribs to provide the forced convection. The numerical computation data of the average heat emission and aerodynamic resistance have been obtained.
Numerical simulation of the convective heat exchange and aerodynamics of the surfaces with the lamellar-split ribbing
Keywords: вынужденная конвекция; аэродинамическое сопротивление; радиоэлектронная аппаратура; РЭА; персональный компьютер; ПК; уравнения Навье-Стокса; forced convection; aerodynamic resistance; lamellar-ribbed surface